Is consumer response to plain/standardised tobacco packaging consistent with framework convention on tobacco control guidelines? A systematic review of quantitative studies. - Martine Stead; Crawford Moodie; Kathryn Angus; Linda Bauld; Ann McNeill; James Thomas; Gerard Hastings; Kate Hinds; Alison O'Mara-Eves; Irene Kwan; Richard I Purves; Stuart L Bryce (PLoS ONE)
Background and objectives Standardised or 'plain' tobacco packaging was introduced in Australia in December 2012 and is currently being considered in other countries. The primary objective of this systematic review was to locate, assess and synthesise published and grey literature relating to the potential impacts of standardised tobacco packaging as proposed by the guidelines for the international Framework Convention on Tobacco Control: reduced appeal, increased salience and effectiveness of health warnings, and more accurate perceptions of product strength and harm. Methods Electronic databases were searched and researchers in the field were contacted to identify studies. Eligible studies were published or unpublished primary research of any design, issued since 1980 and concerning tobacco packaging. Twenty-five quantitative studies reported relevant outcomes and met the inclusion criteria. A narrative synthesis was conducted. Results Studies that explored the impact of package design on appeal consistently found that standardised packaging reduced the appeal of cigarettes and smoking, and was associated with perceived lower quality, poorer taste and less desirable smoker identities. Although findings were mixed, standardised packs tended to increase the salience and effectiveness of health warnings in terms of recall, attention, believability and seriousness, with effects being mediated by the warning size, type and position on pack. Pack colour was found to influence perceptions of product harm and strength, with darker coloured standardised packs generally perceived as containing stronger tasting and more harmful cigarettes than fully branded packs; lighter coloured standardised packs suggested weaker and less harmful cigarettes. Findings were largely consistent, irrespective of location and sample. Conclusions The evidence strongly suggests that standardised packaging will reduce the appeal of packaging and of smoking in general; that it will go some way to reduce consumer misperceptions regarding product harm based upon package design; and will help make the legally required on-pack health warnings more salient.